A sintered graphite sealing material and preparation method thereof
By using nanocarbon fibers and maleic anhydride of polar groups in the preparation of graphite sealing materials, and using specific mixing equipment and processes, the problem of poor mixing effect of ultra-fine coke powder is solved, and the mechanical strength and performance stability of the material are improved.
Patent Information
- Application Number
- CN202411332671.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-09-24
AI Technical Summary
In the preparation process of traditional graphite sealing materials, the particle size of ultrafine acorn powder is too small, resulting in poor mixing effect, and uneven distribution of medium-temperature asphalt, resulting in unstable product performance.
Ultrafine coke powder with a particle size of 5μm-10μm, graphite powder with 20μm-50μm and asphalt coke powder were used, and nanocarbon fibers and maleic anhydride with polar groups were added, and vacuum mixing was carried out through specific mixing equipment and processes to form a better interface bonding and preliminary composite structure.
The mechanical strength, compactness and performance stability of graphite sealing materials are improved, the pore structure and material compatibility are optimized, and the uniform distribution and adhesion of medium-temperature asphalt are enhanced.
Smart Images

Figure CN119143503B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon material processing, in particular to a sintered graphite sealing material and a preparation method thereof. Background Art
[0002] In modern industry, sealing materials play a vital role in preventing fluid or gas leakage. With the promotion of low-carbon concepts and the development of advanced inorganic non-metallic materials, higher requirements and expectations are also put forward for graphite sealing materials. In the context of pursuing low-carbon and environmental protection, the production process of graphite sealing materials needs to pay more attention to energy conservation and emission reduction to reduce the impact on the environment. At the same time, the research results of advanced inorganic non-metallic materials provide new ideas and methods for improving the performance of graphite sealing materials.
[0003] However, there are many problems in the preparation process of traditional graphite sealing materials: the particle size of the coke powder prepared by old-fashioned grinding equipment is about 50μm, which has the disadvantages of loose structure and high porosity; the pressed molding is mostly solid blanks, and the subsequent shaping wastes raw materials; the roasting process is prone to shrinkage deformation and large-scale cracking of large-sized, fine-grained annular products.
[0004] Therefore, the patent with authorization announcement number CN108821770B in the relevant field of C04B discloses a method for preparing a high-performance graphite sealing material; the method is to mix ultrafine coke powder with a particle size of less than 10μm, graphite powder with a particle size of less than 50μm and asphalt coke powder with a particle size of less than 50μm, then add medium-temperature asphalt with a softening point of 70℃-100℃ and a residual carbon rate of 30wt%-50wt%, knead and roll into sheets, crush and grind into powder after cooling, and make pressed powder; press and form through an annular pressing mold, place the annular prefabricated green body in a closed crucible for roasting, and then immerse it after completion. After the immersion is completed, it is loaded into a graphitization furnace for graphitization, and after the graphitization is completed, a graphite sealing material is obtained; the graphite sealing material in the invention is dense and uniform, has good wear resistance, high graphitization degree, high mechanical strength, low porosity, and the molding rate and roasting yield rate are improved, saving raw materials and reducing production costs.
[0005] However, in the above patent, although ultrafine coke powder, graphite powder and asphalt coke powder with finer particle size are used to make graphite sealing materials to achieve the advantages of dense and uniform, good wear resistance, high degree of graphitization, high mechanical strength and low porosity, in the preparation process, the above materials need to be mixed and then kneaded with medium-temperature asphalt; and the current kneading equipment is suitable for coke powder with a particle size of about 50μm. For ultrafine coke powder with a particle size of less than 10μm, the mixing effect is not obvious, which easily causes uneven distribution of medium-temperature asphalt in the mixture, resulting in unstable product performance, such as strength, hardness, wear resistance and other aspects are not as expected; therefore, the present invention proposes a sintered graphite sealing material and a preparation method thereof. Summary of the invention
[0006] The object of the present invention is to provide a sintered graphite sealing material and a preparation method thereof to solve the problems raised in the above background.
[0007] To achieve the above object, the present invention provides the following technical solution: a sintered graphite sealing material, comprising ultrafine coke powder with a particle size of 5 μm-10 μm, graphite powder with a particle size of 20 μm-50 μm, pitch coke powder with a particle size of 20 μm-50 μm, and nano-carbon fiber with a diameter of 50 nm-100 nm and a length of 10 μm-20 μm; and also comprising a binder;
[0008] The binder is medium-temperature asphalt, with a softening point of 80°C-90°C and a residual carbon rate of 35wt%-45wt%; the medium-temperature asphalt contains a polar group, and the polar group is maleic anhydride;
[0009] The weight percentages are as follows: ultrafine coke powder 25%-35%; graphite powder 20%-30%; asphalt coke powder 15%-25%; nano carbon fiber 5%-10%; medium temperature asphalt 15%-25%;
[0010] Among them, maleic anhydride accounts for 5% in medium-temperature asphalt.
[0011] Preferably, a method for preparing a sintered graphite sealing material comprises the following steps:
[0012] S1. Vibrating and screening the ultrafine coke powder, graphite powder and asphalt coke powder according to the set particle size, and performing drying and preheating treatment;
[0013] S2, placing the treated ultrafine coke powder, graphite powder and asphalt coke powder into a kneading device for ultrafine particles, introducing nano-carbon fibers during the placing process; adding heated medium-temperature asphalt and kneading under vacuum;
[0014] The specific method of S2 includes the following steps:
[0015] S21, using a vacuum suction machine to suck the raw materials into the mixing and kneading bin from the corresponding pipes;
[0016] S22, during the raw material transportation process, the medium-temperature asphalt inside the first transportation pipeline is heated by a heater, and the heater transfers part of the heat to the inside of the preheating pipe through a heat conduction pipe to preheat the raw materials inside the second transportation pipeline, the third transportation pipeline, and the fourth transportation pipeline;
[0017] S23, the medium-temperature asphalt in the first delivery pipeline is mixed with the polar groups in the maleic anhydride addition part during the delivery process; the asphalt coke powder in the second delivery pipeline is directly delivered to the mixing bin; the ultrafine coke powder in the third delivery pipeline and the graphite powder in the fourth delivery pipeline are pre-mixed with the nano-carbon fibers in advance through the mixing assembly and then delivered to the mixing bin;
[0018] S24, the variable speed motor drives the kneading blades to rotate through the spline shaft to knead the raw materials in the vacuum environment of the kneading bin;
[0019] S25, during the kneading process, the mixing assembly controls the hinged rod through the cam to apply pressure to one end of the swing frame, causing the swing frame to swing back and forth, and the swing frame controls the kneading blades to slide back and forth on the surface of the spline shaft through the slide, thereby achieving an efficient mixing effect;
[0020] S3, after the kneading is completed, the sheet is rolled, and the sheet is naturally cooled, and then crushed and ground to make a pressed powder; the pressed powder is passed through an annular pressing mold, and a step-by-step pressurization method is adopted to pressurize at room temperature and a pressure of 60MPa-80MPa to obtain an annular prefabricated green body;
[0021] S4. Place the annular prefabricated green body in a closed crucible for roasting, and fill the inside and outside of the crucible with metallurgical coke; then put the roasted green body into a sintering furnace, control the heating rate of the sintering furnace to 5-10℃ / min, heat it to 800-1000℃, keep it warm for 2-3 hours, and cool it to room temperature with the furnace to obtain the final graphite sealing material product.
[0022] Preferably, in S2, the raw materials are kneaded in a kneading chamber under a vacuum environment for 2.5 h-3 h to make the material temperature reach 155° C.-165° C.; and the sheets are rolled at 135° C.-145° C.
[0023] Preferably, the sintering temperature in S4 is 1250° C.-1350° C., and the sintering time is 2-4 hours.
[0024] Preferably, the kneading equipment for ultrafine particles includes a mixing component and an adjusting component, the mixing component includes a servo motor, the output end of the servo motor is sleeved with a transmission belt, the surface of the transmission belt is sleeved with a transmission disk, and the servo motor drives the transmission disk to rotate through the transmission belt; the surface of the transmission disk is fixedly connected to a transmission shaft, and the surface of the transmission shaft is fixedly connected to a stirring blade and a cam.
[0025] Preferably, the adjustment assembly includes a limit plate, a slide and a connecting block, the surface of the limit plate is rotatably connected to a swing frame, the surface of the swing frame is fixedly connected to a regulating rod and a connecting plate, the surface of the regulating rod is fixedly connected to a regulating gear, and the surface of the swing frame is provided with a groove; the surface of the slide is fixedly connected to a snap-in bearing, and one end of the slide slides on the slotted surface through a sleeve shaft; the connecting block rotates on one end of the connecting plate, and the other end of the connecting block rotates on one end of the hinged rod, and the other end of the hinged rod is rotatably sleeved on the surface of the cam.
[0026] Preferably, a kneading device for ultrafine particles also includes a pretreatment component, which includes a preheating pipe and a conveying and adding component; the first conveying pipe, the second conveying pipe, the third conveying pipe and the fourth conveying pipe are all inserted into the preheating pipe; a heater is provided on the surface of the first conveying pipe, a heat conducting pipe is provided on the surface of the heater, and one end of the heat conducting pipe is fixed to the surface of the preheating pipe; a maleic anhydride adding part is provided through one end of the first conveying pipe, and one end of the maleic anhydride adding part is connected through the first connecting pipe.
[0027] Preferably, the surface of the third conveying pipeline is provided with a first quantity control valve and a second connecting pipe, one end of the second connecting pipe is connected with an upper T-shaped connecting pipe, the lower part of the upper T-shaped connecting pipe is connected with a sealing disk, the surface of the sealing disk is rotatably connected with a mixing bin, and the surface of the mixing bin is fixedly provided with a transmission protrusion; the lower part of the sealing disk is connected with a lower T-shaped connecting pipe, and the surface of the lower T-shaped connecting pipe is connected with a third connecting pipe; the conveying and adding component includes a nano-carbon fiber silo, a conveyor is provided below the nano-carbon fiber silo, the surface of the conveyor is connected with a quantity control terminal, the surface of the quantity control terminal is connected with a fourth connecting pipe, one end of the fourth connecting pipe is connected to the surface of the upper T-shaped connecting pipe; a quantity control ball is provided inside the quantity control terminal, a through hole is opened inside the quantity control ball, and a quantity control gear is fixedly connected to the surface of the quantity control ball; the quantity control gear is meshingly connected with the regulating gear.
[0028] Preferably, a kneading device for ultrafine particles also includes a kneading machine, the kneading machine includes a variable speed motor and, a driving gear is fixedly provided at the output end of the variable speed motor, a driven gear is meshed and driven on the surface of the driving gear, a spline shaft is fixedly connected to the surface of the driven gear, an arc block is fixedly connected to one end of the spline shaft, and a kneading blade is slidably connected to the surface of the spline shaft; a driving strip is provided on the surface of the H-shaped slide, an arc-shaped matching protrusion is fixedly provided on the surface of the H-shaped slide, and the arc-shaped matching protrusion is meshed and slidably connected with the arc block; the arc-shaped matching protrusion slides on the inner surface of the support frame, and a reset spring is provided inside the support frame.
[0029] Preferably, a kneading device for ultrafine particles also includes a supporting bottom plate, a kneading box and a protective box; the kneading box includes a kneading bin, a temperature-controlled heater and a vacuum suction machine are arranged above the kneading bin, and a discharge port is arranged below the kneading bin; the kneading box, the kneading machine and the protective box are fixed above the supporting bottom plate; the pretreatment component, the mixing component and the regulating component are fixedly arranged inside the protective box.
[0030] The beneficial effects of the present invention are as follows:
[0031] 1. The present invention adds an appropriate amount of nano-carbon fibers and polar groups when making graphite sealing materials; during the kneading process of related materials, the nano-carbon fibers can improve the dispersibility of ultrafine coke powder, reduce agglomeration, improve the mechanical strength of graphite sealing materials, and optimize the pore structure to make the product denser; the polar groups can improve compatibility, promote the uniform distribution of medium-temperature asphalt, enhance adhesion to improve the integrity and stability of the material, improve surface activity, and optimize material performance.
[0032] 2. The present invention improves the mixing effect of ultrafine coke powder with a particle size of less than 10 μm through a kneading device for ultrafine particles; the device uses a vacuum suction machine to transport various materials weighed by a metering device according to the addition ratio of various raw materials to a kneading bin through a separate pipeline; during the transportation process, each material is preheated, and nano-carbon fibers are added to the ultrafine coke powder and graphite powder in advance for mixing and stirring, which helps to form a better interface bonding, form a preliminary composite structure, and improve the compatibility and interaction of materials.
[0033] 3. The present invention changes the traditional stirring and kneading mode, adjusts the kneading blades from a single working position to a reciprocating sliding state to stir and knead various materials, and reduces the problem of agglomeration of 10μm ultrafine coke powder; at the same time, in the process of the spline shaft driving the kneading blades to rotate and knead, the reciprocating motion of the H-shaped slide is controlled by the mutual engagement of the arc block and the arc surface of the arc matching convex block. In this process, the rotation of the mixing chamber is controlled by the card-connected transmission of the drive bar and the transmission convex block, further improving the mixing effect of ultrafine coke powder, graphite powder and nano-carbon fiber. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 A schematic flow chart of the steps of a method for preparing a sintered graphite sealing material;
[0035] Figure 2 This is a schematic flow chart of step S2 in a method for preparing a sintered graphite sealing material;
[0036] Figure 3 It is a schematic diagram of the kneading box structure;
[0037] Figure 4 It is a schematic diagram of the local structure of the preprocessing component;
[0038] Figure 5 It is a schematic diagram of the local structure of the pre-treatment component and the mixing component;
[0039] Figure 6 It is a schematic diagram of the local structure of the hybrid component;
[0040] Figure 7 It is a schematic diagram of the structure of a kneading machine;
[0041] Figure 8 It is a schematic diagram of the H-type slide structure;
[0042] Fig. 9 It is a schematic diagram of the structure of the mixing bin;
[0043] Fig.10 It is a schematic diagram of the structure of the adjustment component;
[0044] Fig.11 This is a schematic diagram of the control terminal structure;
[0045] Fig.12 This is a schematic diagram of the internal structure of the control terminal;
[0046] Fig.13 It is a schematic diagram of the external structure of the kneading equipment;
[0047] In the figure: 1. Support bottom plate; 2. Kneading box; 21. Kneading bin; 22. Temperature control heater; 23. Discharge port; 24. Vacuum suction machine; 3. Kneading machine; 31. Variable speed motor; 32. Driving gear; 33. Driven gear; 34. Spline shaft; 341. Arc block; 35. Kneading blade; 36. H-type slide; 361. Drive bar; 362. Arc matching convex block; 363. Support frame; 364. Return spring; 4. Protection box; 5. Pretreatment component; 51. Preheating pipe; 52. First conveying pipeline; 521. Heating machine; 522. Heat conducting pipe; 523. Maleic anhydride adding part; 524. First connecting pipe; 53. Second conveying pipeline; 54. Third conveying pipeline; 541. First quantity control valve; 542. Second connecting pipe; 543. Upper T-type connecting pipe ; 544, sealing disk; 545, mixing bin; 5451, transmission cam; 546, lower T-type connecting pipe; 547, third connecting pipe; 55, fourth conveying pipeline; 56, conveying and adding component; 561, nano carbon fiber silo; 562, conveyor; 563, quantity control terminal; 5631, quantity control gear; 5632, quantity control ball; 5633, through hole; 564, fourth connecting pipe; 6, mixing component; 61, servo motor; 62, transmission belt; 63, transmission disk; 64, transmission shaft; 65, stirring blade; 66, cam; 7, adjustment component; 71, limit plate; 72, swing frame; 721, control rod; 7211, control gear; 722, slot; 723, connecting plate; 73, slide; 731, snap-on bearing; 74, connecting block; 75, hinged rod. DETAILED DESCRIPTION
[0048] Although the prior art uses ultrafine coke powder, graphite powder and asphalt coke powder with finer particle size to make graphite sealing materials, achieving the advantages of dense and uniform, good wear resistance, high graphitization degree, high mechanical strength and low porosity, in the preparation process, the above materials need to be mixed and then kneaded with medium-temperature asphalt; and the current kneading equipment is suitable for coke powder with a particle size of about 50 μm, and the mixing effect is not obvious for ultrafine coke powder with a particle size of less than 10 μm, which easily causes uneven distribution of medium-temperature asphalt in the mixture, resulting in unstable product performance, such as strength, hardness, wear resistance and other aspects are not as expected;
[0049] Therefore, the present invention provides a sintered graphite sealing material and a preparation method thereof.
[0050] Embodiment 1:
[0051] Ultrafine coke powder with a particle size of 5μm-10μm, graphite powder with a particle size of 20μm-50μm, asphalt coke powder with a particle size of 20μm-50μm, and nano-carbon fiber with a diameter of 50nm-100nm and a length of 10μm-20μm are selected; medium-temperature asphalt is selected as a binder, with a softening point of 80℃-90℃ and a residual carbon rate of 35wt%-45wt%; the medium-temperature asphalt contains polar groups, and the polar groups are maleic anhydride;
[0052] Table 1: Weight percentage of each material
[0053]
[0054] As shown in Table 1, the weight percentages are as follows: ultrafine coke powder 25%-35%; graphite powder 20%-30%; asphalt coke powder 15%-25%; nano-carbon fiber 5%-10%; medium-temperature asphalt 15%-25%;
[0055] Among them, maleic anhydride accounts for 5% in medium-temperature asphalt.
[0056] Figure 1 and Figure 2 The specific implementation steps are as follows: vibrating and screening the ultrafine coke powder, graphite powder and asphalt coke powder according to the set particle size, and performing drying and preheating treatment;
[0057] The pretreated ultrafine coke powder, graphite powder, asphalt coke powder and nano-carbon fiber are transported to a vacuum kneading device, and a medium-temperature asphalt with a softening point of 80°C-90°C and a residual carbon rate of 35wt%-45wt% is added, wherein the medium-temperature asphalt contains maleic anhydride; kneading is performed under a vacuum environment for 2.5h-3h to make the material temperature reach 155°C-165°C; after kneading, sheeting is performed at 135°C-145°C, and the sheeting is naturally cooled after sheeting, and then crushing and grinding are performed to make pressed powder; the pressed powder is passed through an annular pressing mold, and is pressed and formed at room temperature and a pressure of 60MPa-80MPa by a step-by-step pressurization method to obtain an annular prefabricated green body.
[0058] The annular prefabricated green body is placed in a closed crucible and roasted in a step-by-step slow heating method, and the inside and outside of the crucible are filled with metallurgical coke; the roasted green body is placed in a sintering furnace with uniform heating; the sintering temperature is controlled at 1250℃-1350℃, the sintering time is 2-4 hours, the heating rate of the sintering furnace is controlled at 5-10℃ / min, the temperature is raised to 800-1000℃, the temperature is kept for 2-3 hours, and the furnace is cooled to room temperature to obtain the final graphite sealing material product; as shown in Table 2, the product has the following data through performance testing:
[0059] Table 2: Comparison table of performance index test results of the product of the present invention and conventional products
[0060]
[0061] Embodiment 2:
[0062] In the pretreatment process of ultrafine coke powder, graphite powder, asphalt coke powder and medium temperature asphalt transportation, such as Figure 3 and Figure 4 As shown, the vacuum suction machine 24 is started, and various raw materials that have been accurately weighed are sucked into the mixing chamber 21 through the corresponding first conveying pipe 52, the second conveying pipe 53, the third conveying pipe 54 and the fourth conveying pipe 55 according to the set ratio;
[0063] The first delivery pipeline 52 delivers medium-temperature asphalt, which is heated by the heater 521 and preheats other pipes in the preheating pipe 51 through the heat pipe 522; the second delivery pipeline 53 directly delivers the asphalt coke powder to the inside of the kneading bin 21;
[0064] like Figure 5 As shown, the ultrafine coke powder in the third conveying pipeline 54 and the graphite powder in the fourth conveying pipeline 55 are pre-mixed with the nano-carbon fibers through the mixing assembly 6 during the conveying process;
[0065] The servo motor 61 is started to drive the transmission disc 63 to rotate through the transmission belt 62; Figure 6 As shown, the transmission disc 63 rotates to drive the stirring blade 65 and the cam 66 on the transmission shaft 64 to rotate; the stirring blade 65 stirs and mixes the pre-mixed materials;
[0066] like Figure 7 As shown, the variable speed motor 31 is started, and the spline shaft 34 is driven to rotate through the driving gear 32 and the driven gear 33, and the kneading blades 35 on the spline shaft 34 begin to rotate to knead the material in the kneading bin 21;
[0067] At the same time, Figure 8 As shown, the rotation of the spline shaft 34 drives the arc block 341 to rotate synchronously. Since the arc block 341 is engaged with the arc matching protrusion 362, and the arc matching protrusion 362 is limited by the support frame 363, the arc matching protrusion 362 slides inside the support frame 363 and is reset by the reset spring 364, thereby realizing the reciprocating sliding effect of the H-shaped slide 36.
[0068] like Fig. 9 As shown, when the H-shaped slide 36 slides back and forth, the driving bar 361 squeezes the driving protrusion 5451 on the surface of the mixing chamber 545, causing the mixing chamber 545 to rotate, thereby further improving the mixing effect of the ultrafine coke powder and graphite powder with the nano-carbon fiber;
[0069] like Fig.10As shown, during the kneading process, the cam 66 rotates to control the hinged rod 75 to apply pressure to one end of the swing frame 72, so that the swing frame 72 swings back and forth; the swing frame 72 controls the kneading blade 35 to slide back and forth on the surface of the spline shaft 34 through the clamping bearing 731 on the surface of the slide 73, thereby achieving a more efficient kneading effect;
[0070] like Fig.11 and 12 As shown, the quantity control gear 5631 is meshedly connected with the regulating gear 7211. As the regulating gear 7211 rotates, the quantity control ball 5632 is controlled to rotate, and the addition of nano-carbon fibers is intermittently controlled to improve uniformity.
[0071] The above-mentioned embodiments only express the implementation methods of the present invention, and cannot be understood as limiting the scope of the invention patent, nor is it any form of limitation on the structure of the present invention. It should be pointed out that for ordinary technicians in this field, several changes and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A method for preparing a sintered graphite sealing material, characterized in that: The following steps are involved: S1. Vibration screening, drying and preheating of ultrafine coke powder of 5μm-10μm, graphite powder of 20μm-50μm and asphalt coke powder of 20μm-50μm according to set particle size; S2, placing the processed raw materials into a kneading device for ultrafine particles for vacuum kneading; S3, rolling the mixed and kneaded pieces, cooling, crushing and grinding the pieces into pressed powder, and using an annular mold to press-form the pressed powder in steps to obtain an annular prefabricated green body; S4, roasting and sintering the annular prefabricated green body, heating it to 800-1000° C., keeping it warm, and cooling it to obtain a graphite sealing material product; Wherein, S2 includes the following steps: S21, the vacuum suction machine sucks the raw materials from the corresponding pipeline into the kneading bin; S22, heating medium-temperature asphalt, and heat pipe preheating other pipeline raw materials; S23, medium temperature asphalt is mixed with maleic anhydride, asphalt coke powder is directly transported, and ultrafine coke powder, graphite powder and nano carbon fibers with a diameter of 50nm-100nm and a length of 10μm-20μm are pre-mixed and then transported; S24, the variable speed motor drives the kneading blades to rotate and knead; S25, during kneading, the kneading blades are made to slide back and forth by adjusting the components to achieve efficient mixing; The kneading device for ultra-fine particles comprises a mixing component (6) and an adjusting component (7); the mixing component (6) comprises a servo motor (61); a transmission belt (62) is sleeved on the output end of the servo motor (61); a transmission disc (63) is sleeved on the surface of the transmission belt (62); the servo motor (61) drives the transmission disc (63) to rotate via the transmission belt (62); a transmission shaft (64) is fixedly connected to the surface of the transmission disc (63); a stirring blade (65) and a cam (66) are fixedly connected to the surface of the transmission shaft (64); The adjustment assembly (7) comprises a limit plate (71), a slide (73) and a connecting block (74); the surface of the limit plate (71) is rotatably connected to a swing frame (72); the surface of the swing frame (72) is fixedly connected to a regulating rod (721) and a connecting plate (723); the surface of the regulating rod (721) is fixedly connected to a regulating gear (7211); and the surface of the swing frame (72) is provided with a slot (722); the surface of the slide (73) is fixedly connected to a clamping bearing (731); one end of the slide (73) slides on the surface of the slot (722) via a sleeve shaft; the connecting block (74) rotates on one end of the connecting plate (723); the other end of the connecting block (74) rotates on one end of a hinged rod (75); the other end of the hinged rod (75) is rotatably sleeved on the surface of a cam (66); The kneading device for ultra-fine particles also includes a kneading machine (3), the kneading machine (3) including a variable speed motor (31) and an H-shaped slide (36), the output end of the variable speed motor (31) being fixedly provided with a driving gear (32), the surface of the driving gear (32) being meshingly driven with a driven gear (33), the surface of the driven gear (33) being fixedly connected with a spline shaft (34), one end of the spline shaft (34) being fixedly connected with an arc block (341), the surface of the spline shaft (34) being slidably connected with a kneading blade (35); the surface of the H-shaped slide (36) being provided with a driving strip (361), the surface of the H-shaped slide (36) being fixedly provided with an arc-shaped matching protrusion (362), the arc-shaped matching protrusion (362) being meshingly connected with the arc block (341); the arc-shaped matching protrusion (362) slidingly connected with the arc block (341); the arc-shaped matching protrusion (362) slidingly sliding on the inner surface of a support frame (363), the interior of the support frame (363) being provided with a return spring (364).
2. The method for preparing a sintered graphite sealing material according to claim 1, characterized in that: In S2, the raw materials are kneaded in a kneading chamber (21) under a vacuum environment for 2.5 hours to 3 hours to make the material temperature reach 155° C. to 165° C.; and the raw materials are rolled at 135° C. to 145° C.
3. The method for preparing a sintered graphite sealing material according to claim 1, wherein the kneading device for ultrafine particles further comprises a pretreatment component (5), wherein the pretreatment component (5) comprises a preheating tube (51) and a conveying and adding component (56); a first conveying pipeline (52), a second conveying pipeline (53), a third conveying pipeline (54) and a fourth conveying pipeline (55) are all arranged inside the preheating tube (51); a heater (521) is arranged on the surface of the first conveying pipeline (52), a heat conducting pipe (522) is arranged on the surface of the heater (521), and one end of the heat conducting pipe (522) is fixed to the surface of the preheating tube (51); a maleic anhydride adding part (523) is arranged through one end of the first conveying pipeline (52), and one end of the maleic anhydride adding part (523) is connected through the first connecting pipe (524).
4. The method for preparing a sintered graphite sealing material according to claim 3, characterized in that: The surface of the third delivery pipeline (54) is provided with a first control valve (541) and a second connecting pipe (542); one end of the second connecting pipe (542) is connected to an upper T-shaped connecting pipe (543); a sealing disk (544) is connected to the lower part of the upper T-shaped connecting pipe (543); a mixing chamber (545) is rotatably connected to the surface of the sealing disk (544); a transmission lug (5451) is fixedly provided to the surface of the mixing chamber (545); a lower T-shaped connecting pipe (546) is connected to the lower part of the sealing disk (544); a third connecting pipe (547) is connected to the surface of the lower T-shaped connecting pipe (546); the delivery and addition component (56) comprises nano-carbon fibers. A carbon fiber silo (561) is provided below the carbon fiber silo (561), a conveyor (562) is provided, a surface of the conveyor (562) is connected through a quantity control terminal (563), a surface of the quantity control terminal (563) is connected through a fourth connecting tube (564), one end of the fourth connecting tube (564) is connected through the surface of the upper T-shaped connecting tube (543); a quantity control ball (5632) is provided inside the quantity control terminal (563), a through hole (5633) is provided inside the quantity control ball (5632), a quantity control gear (5631) is fixedly connected to the surface of the quantity control ball (5632); the quantity control gear (5631) is meshingly connected to the regulating gear (7211).
5. The method for preparing a sintered graphite sealing material according to claim 4, characterized in that: The kneading device for ultra-fine particles further comprises a supporting bottom plate (1), a kneading box (2) and a protective box (4); the kneading box (2) comprises a kneading bin (21), a temperature-controlled heater (22) and a vacuum suction machine (24) are arranged above the kneading bin (21), and a discharge port (23) is arranged below the kneading bin (21); the kneading box (2), the kneading machine (3) and the protective box (4) are fixed above the supporting bottom plate (1); and the pretreatment component (5), the mixing component (6) and the regulating component (7) are fixedly arranged inside the protective box (4).
6. The sintered graphite sealing material prepared by the method for preparing a sintered graphite sealing material according to any one of claims 1 to 5, wherein the weight percentage of raw materials is: ultrafine coke powder 25%-35%; graphite powder 20%-30%; asphalt coke powder 15%-25%; nano-carbon fiber 5%-10%; medium-temperature asphalt 15%-25%; in, Maleic anhydride accounts for 5% in medium-temperature asphalt.
Citation Information
Patent Citations
A method for preparing a high-performance graphite sealing material
CN108821770B
Preparation method for high-performance graphite sealing material
CN108821770A
Composite modified high-viscosity asphalt and preparation method thereof
CN116426135A